Design, Manufacture, and Testing of Force Plate with Affordable Price - Uwieto, Pandi
Force plate is one of instruments often used in gait analysis, standing balance analysis, and sport biomechanic analysis. But, until now there is no force plate producer in Indonesia. Some force plate producer like AMTI, Bertec, and Kistler, but they arequite expensive because the average price of the offered force plate is above Rp 500.000.000,- (five hundred million rupiah). Therefore, in this research, an affordable force plate was developed. The force plate could measure vertical Ground Reaction Force (GRF) with a capacity of 4800 N. Furthermore, it could also be employed to determine Centre of Pressure (CoP) which is needed in standing balance analysis. The developed force plate was validated through measurement of GRF for standing, walking, and jumping. The force plate is also used to obtain the stability of a person standing with two feet and one foot on the ground Moreover, in this study, a three axis load cell that could measure force in three directions (Fx, Fy, and Fz) was developed. This load cell could be the basis for development of a six axes force plate (Fx, Fy, Fz, Mx, My, dan Mz).. The developed load cell was tested using tensile testing machine and the results were comparable to the stressed obtained via finite element analysis.